Retention of Plasminogen Activator and Acid Phosphatase in Lysosomes of Lipemic Rats - Beard, E. L (Thrombosis and Haemostasis, 1971)
The effect of chronic lipemia on lysosomal permeability was investigated. Rats were fed either 40% butter, 40% corn oil, atherogenic, thrombogenic or normal diet for 9 months. Prior to sacrifice, half of each diet group was injected with acid phosphatase to increase lysosomal lability. Blood and liver lysosome isolated were assayed for lysosomal enzyme levels. Only lysosomes from rats fed the normal diet responded to acid phosphatase injections by releasing increased quantities of plasminogen activator and acid phosphatase from liver lysosomes into the blood. It was concluded that chronic hypercholesterolemia and elevated blood phospholipid levels increased the integrity of lysosomal membranes and interfered with release of the hydrolytic enzymes retained by them.